PREVALENCE OF HAEMAPROTOZOANS AND THEIR ASSOCIATED RISK FACTORS IN DISTRICT KOHAT (Journal of Medical & Health Sciences Review, 2025)
Aim: This work represents the general overview on heamoproyozoans in small ruminants of different area of District ,Kohat Khyber Pakhtunkhwa, Pakistan,which help in avoid the socioeconomics lost in livestock.Study area and duration: the study area of this work is District Kohat, Khyber Pakhtunkhwa, specimens was collected from different area of District Kohat ,Khyber Pakhtunkhwa, Pakistan, and specimens was collected from January to June.Study design: A total of blood Samples (n=319) as well as ticks were randomly collected from small ruminants of District,Kohat Khyber Pakhtunkhwa, Pakistan with a prescribed performa filled for each sample in order to calculate the position of heamoprotozoans infection from January 2024 to June 2024 in different, age groups,month, locality, tick infestation etc.. The blood samples were stained through giemsa stain and were observed under microscope at 60X and 100X magnification with use of immersion oil.Results: The prevalence of heamoprotozoans in small ruminants of District, Kohat Khyber Pakhtunkhwa, Pakistan, is 8.15, main factor of which is ticks. The infested animals is mostly at the risks of the desired diseases because ticks act as vector for transmission of these diseases. This study examines infection prevalence across various factors, including gender, age,region, tick infestation, parasite species, and environmental variables. Significant findings highlight higher infection rates in females, older animals, rural areas, and open grazing systems. Seasonal patterns and coat color also influence susceptibility. The results underscore the need for targeted strategies to control infection based on these risk factors.Conclusion: According to the result, it may be concluded that haemoprotozoan infection in small ruminants is highly prevalent in District, Kohat Khyber Pakhtunkhwa, Pakistan, and produces clinicopathological lesions in small ruminants.So proper control measures should taken to reduce the prevalence of haemoprotozoa of duck in District, Kohat Khyber Pakhtunkhwa, Pakistan.